Is the Welfare State Bad for Citizens’ Moral Character? Beliefs and Evidence - Kimmo Eriksson; Brent Simpson (Socius)
Conservative thinkers have long warned that the welfare state may weaken society’s moral fiber. But this claim has not been empirically examined. The authors link publicly available data on the sizes of welfare states with behavioral data from a recent study in which thousands of lost wallets were distributed in 40 countries to measure how often they were returned to their owners. A preregistered study ( n  = 194) confirmed that U.S. Republicans perceive returning lost wallets as a good indicator of moral character and believe that people’s moral character is worse in countries where the welfare state is larger. Contrary to this belief, the linked data indicate a strong positive relationship between the size of welfare states and moral character: rates of returned wallets were higher in countries with historically large welfare states, net of economic prosperity and economic inequality. The authors conclude with tentative implications and suggestions for further work.